Electronic properties and stability phase diagrams for cubic BN surfaces. Issue 4 (4th March 2017) - Mohammadpour, Ehsan; Altarawneh, Mohammednoor; Jiang, Zhong-Tao; Mondinos, Nicholas; Dlugogorski, Bogdan Z.
Abstract: This contribution investigates structural and electronic properties as well as stability phase diagrams of surfaces of the cubic boron nitride ( c -BN). Our calculated parameters for bulk c -BN agree reasonably well with both experimental and computed values available in the literature. Based on the energies of the three experimentally recognised phases of bulk boron, i.e. α -B36, β -B105 and γ -B28, we estimate enthalpy of formation of c -BN to be −2.8 eV. The c -BN(1 0 0) surface offers separate B and N terminations (denoted as c -BN(1 0 0)_B and c-BN(1 0 0)_N), whereas c -BN(1 1 1) and c -BN(1 1 0) are truncated with combinations of boron and nitrogen atoms (denoted as c -BN(1 1 1)_BN and c -BN(1 1 0)_BN). Optimised geometries of surfaces display interlayer displacements up to the three topmost layers. Downward displacement of surface boron atoms signifies a common geometric feature of all surfaces. Bulk c -BN and its most stable surface c -BN(1 0 0)_N possess no metallic character, with band gaps of 5.46 and 2.7 eV, respectively. We find that, only c -BN(1 0 0)_B configuration exhibits a metallic character. c -BN(1 1 0)_BN and c -BN(1 1 1)_BN surfaces display corresponding band gaps of 2.5 and 3.9 eV and, hence, afford no metallic property.